2001
DOI: 10.1021/om010491b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Photochemical Cyclopropanation of Alkenes with Methyl Diazo(trialkylsilyl)acetates:  Steric Effects and Thermodynamic Stabilities of Cyclopropanes

Abstract: Diazo esters 1 (N 2 dC(SiR 3 )COOMe; R ) Me (1a), Et (1b), i-Pr (1c)) have been decomposed in styrene, 1-hexene, and cyclohexene under Cu, Rh, or Ru catalysis as well as by photochemical means with the objective to evaluate the effectiveness and diastereoselectivity of the respective cyclopropanation reaction. With styrene and 1-hexene as substrates, the ability of the catalysts followed the order CuOTf > [Ru 2 (CO) 4 (µ-OAc) 2 ] n ≈ Rh 2 (OAc) 4 , but even CuOTf (copper(I) triflate) did not promote cyclopropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The color of the ''white polymer'', its solubility in diethyl ether, and an IR absorption at 2153 cm À1 , which is typical for axial carbonyl ligands in complexes of type 2 [15], are not in accord with the properties of 1d prepared by us, and we assume that these authors had prepared the hexacarbonyl complex 2d (L = CO). In fact, we found that heating of Ru 3 (CO) 12 with trifluoroacetic acid at reflux temperature yields 2d (L = CO) which even after prolonged treatment at 180°C/0.001 mbar does not completely release the two axial CO ligands.…”
Section: Catalystsmentioning
confidence: 92%
See 3 more Smart Citations
“…The color of the ''white polymer'', its solubility in diethyl ether, and an IR absorption at 2153 cm À1 , which is typical for axial carbonyl ligands in complexes of type 2 [15], are not in accord with the properties of 1d prepared by us, and we assume that these authors had prepared the hexacarbonyl complex 2d (L = CO). In fact, we found that heating of Ru 3 (CO) 12 with trifluoroacetic acid at reflux temperature yields 2d (L = CO) which even after prolonged treatment at 180°C/0.001 mbar does not completely release the two axial CO ligands.…”
Section: Catalystsmentioning
confidence: 92%
“…We have prepared butyrato complex 1b analogously by heating of Ru 3 (CO) 12 in an excess of butyric acid (Scheme 2, Eq. (1)).…”
Section: Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diastereoselective syn-cyclopropanation of olefins with diazo acetate [112,113], according to Eq. (37), or with silylated diazo esters [114] is catalyzed by the [Ru 2 (CO) 4 (OOCMe) 2 ] n polymer or the complex Fig. 30.…”
Section: Catalytically Active Ru 2 (Co) 4 Complexesmentioning
confidence: 99%